Making Street Name Boards to Make It Easier for The Public to Find Address in Bukit Batu Village, Mantangai District, Kapuas District - Yannur, Khairi; Julianti, Silvia Tri; Nisa, Jahratun; Aprianti, Siti; Prasetyo, Pinki; Bagdadi, Muhammad; Putri, Chantika Nova Scayh; Hafifah, Rabiatul; Putri, Anisa Maharani; Latifah, Nor (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This research aims to address the lack of street nameplates in Bukit Batu Village, Mantangai District, Kapuas Regency, which causes difficulty in locating addresses. KKN students from Palangkaraya State Islamic Institute took the initiative to design and install street signs to solve this issue.Method: The study involved community interaction and field observations. It included surveying areas without nameplates, designing appropriate signs, and installing them in the village.Practical Applications: Installing street signs improves navigation for residents and visitors. This project can serve as a model for similar villages facing the same issue.Conclusion: The research successfully provided a practical solution to the lack of street nameplates, enhancing accessibility in Bukit Batu Village.